Kilba equational sentences - Russell G. Schuh (LibraryPress@UF, 1983)
Kilba, a Chadic language of Gongola State, Nigeria, has a number of enclitic particles which one can reasonably argue function as copulas in equational sentences. Li and Thompson [1977] have described a widespread phenomenon in language history whereby anaphoric elements become copulas. The copular particles of Kilba present a particularly interesting case of this phenomenon in that, first, proximal/distal distinctions of the demonstratives from which the copulas derive have shifted to tense distinctions in equational sentences, and second, the original pronominal and the innovative copular functions are not clearly separable, creating functional ambiguity.